1997
DOI: 10.1155/1997/642360
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Glycosulphatases and Sulphomucin Degradation

Abstract: The presence of a high bacterial population in a region of the gastrointestinal tract is usually associated with the secretion of sulphomucins into the mucus gel covering that region. The term 'sulphomucin' is a histochemical description of the staining properties of mucin. At present this term can only be qualitatively related to the percentage of sulphate in the mucin molecule, which makes the term difficult to use in a biochemical and functional sense. Sulphomucins are thought to carry out the normal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 33 publications
1
101
0
6
Order By: Relevance
“…demonstrated that strains of P. aeruginosa and B. cepacia, isolated from CF patients, can desulfate mucin through mucin sulfatase. After desulfation, mucin may become susceptible to bacterial proteinases and glycosidases generating amino acids and carbohydrates for bacterial consumption (24,25). To our knowledge, however, OCS has not been reported as a product of mucin degradation.…”
Section: Discussionmentioning
confidence: 95%
“…demonstrated that strains of P. aeruginosa and B. cepacia, isolated from CF patients, can desulfate mucin through mucin sulfatase. After desulfation, mucin may become susceptible to bacterial proteinases and glycosidases generating amino acids and carbohydrates for bacterial consumption (24,25). To our knowledge, however, OCS has not been reported as a product of mucin degradation.…”
Section: Discussionmentioning
confidence: 95%
“…It is suggested that sulfomucins are able to reduce the rate at which microflora degrade mucins (Robertson and Wright, 1997) as the high sulfate content of sulfomucins decrease its susceptibility to bacterial glycosidases, limiting the rate and extent of mucin degradation (Hino et al, 2012). Sulfomucins predominated over sialomucins in the colon of the African elephant, A. spinosissimus, cat, dog, some primates and rodent species, whereas mixed acid mucins predominated in the colon of C. cyanea species ( Table 5) in accordance to the Meriones species of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Goblet cells can be separated histologically into neutral or acidic mucin-producing types, and the latter can be divided into sulphated or sialylated mucin-producing subtype (Kiernan, 1990). There is evidence that acidomucins (primarily sulfomucins) restrict mucolysis because of their resistance to degradation by bacterial glycosidases and host proteases (Robertson & Wright, 1997). Therefore, it was hypothesized that the number of total acidic mucin-containing goblet cells may have been elevated in the C. perfringens-challenged chickens because of protective properties against pathogens of acidomucin (Conour et al, 2002), and high bacterial populations have been associated with increased secretion of sulphomucins (Robertson & Wright, 1997).…”
Section: Discussionmentioning
confidence: 99%